Using crop modeling to find solutions for wheat diseases: A review - Ajilogba, Caroline Fadeke; Walker, Sue (Frontiers in Environmental Science, 2023)
Plant diseases have caused serious challenges in the production of food globally. This has led to hunger and food insecurity. Different solutions to crop diseases have been introduced in the recent pasts that include cultural control using farm management methods, chemical control, resistant cultivars and recently biocontrol. Each of these solutions also have varied weaknesses. Faced with the change in climate and the recurrences of crop diseases, new strategies that will incorporate preventive measures would be important in reducing risks to crop production from crop diseases, thus alleviating food insecurity. Various ideas for prevention of these diseases and / or forecasting favorable environmental conditions that enhance disease development has not been fully employed in order for preventive measures to be taken. The use of crop modelling has been used to advise farmers on planting procedures that would bring maximum yields using different management procedures at a farm level. Little is known about the use of crop models in crop disease control. In order to increase the use of crop models for these objectives, this review provides a current status quo and will help to stimulate more research in this regard.